A biblical approach to social transformation - Bellingham, George Robert (1987)
Includes bibliographical references.
In partial fulfillment of the requirements for the degree, Doctor of Ministry, presented to the Faculty of Eastern Baptist Theological Seminary, April 1987.
Keywords: Social change -- biblical teaching